Analysing the future energy performance of residential buildings in the most populated Italian climatic zone: A study of climate change impacts - Mamak P. Tootkaboni (Elsevier, 2021)
There is growing concern that global warming will change the building’s performance pattern in the future. This paper investigates the effects of climate changes on the heating and cooling energy demand, the overall energy performance and the overheating risk of typical residential buildings (existing and refurbished) in the biggest city of the most populated Italian climatic zone, Milan. The widely used morphing methodology was adapted for creating future weather data for different scenarios. Energy performance analysis was carried out using dynamic simulation for the near term (2021–2040) and the long term (2081–2099) periods. The results show decreases in heating energy demand up to 30.9%, intense increases in cooling energy demand, up to 255.1% and significant increases of overheating risk up to 155%. In addition, the effect of refurbishment on each parameter is also analysed and reported. The research demonstrates that climate change causes a paradigm shift in the building energy performance, while the magnitude of climate change impact is not equal for different building types, time periods, insulation levels, and future weather scenarios. Therefore, climate change must be considered for future energy performance assessment of buildings.